Big-five personality and leader-member exchange among employees in hotel industry - Guina, Mariel V. (Animo Repository, 2003)
Various work and attitudinal factors have already been reported as antecedents of LMX or Leader-Member Exchange. Yet, personality had always remained unexplored in terms of its relationship to this new perspective of leadership, LMX. The relational element of leader-member exchange highlights the possible effect of personality to such variable. While the limited studies that attempted to identify possible contribution of high-quality relationship between a leader and his/her member in the Philippine setting also warrants the conduct of this study. So, with the organizing structure of Big Five Personality Factors through NEO PI-R, this study explores the possible personality predictors of LMX among 119 leader-member dyads in the hotel industry. Out of thirty facets of NEO PI-R, only 5 facets were reported by the Stepwise Regression Analysis as statistically significant predictors of LMX. Their contribution to the variation of LMX was not that strong. Specifically, action, deliberation, warmth, positive emotion and assertiveness came out as predictors. Among the five major domains, the domain of extraversion has the most salient facets in this study. And it was reported as the strongest predictor of LMX among the domains. Out of the five, only the domains of conscientiousness and extraversion emerged as predictors of LMX. Such results were expected with the kind of jobs that the participants engage into. This study also identifies possible congruencies between the personality predictors and LMXs of leaders and members. Only measures of LMX from the point of view of the members gave positive results.